Model of Parents’ and Teachers’ Cooperation in Developing Learners’ Religious Character - Febriani, Afifah; Rosdi, Adawiyah; Ottilapoyil, Shanajasmin; Mayesta, Maia; Zulfikri, Zulfikri (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2022)
Parents and teachers are the most prominent figures influencing learners’ religious character as parents are the first teachers for children since childhood. Moreover, teachers play an essential role in developing learners’ character for they dominantly engage with children during their educational phase. Thus, cooperation between these two figures is highly required for religious character formation in living their future phase. This research aims to find an appropriate platform on how to model the cooperation between parents and teachers to educate the religious character. This research employs a qualitative method with a case study approach in four selected elementary schools in one of the Indonesian cities. The source of data was taken using in-depth interviews with fifteen informants (six parents, six teachers, and three students) selected using the purposive sampling technique. In addition, the research team also conducted direct observation at the research location to reinforce the interviews. All interview and observation data were thematically analyzed using the Miles and Huberman interactive analysis model. The research findings found eight models of cooperation carried out by parents and teachers in educating the religious character of students, namely, getting used to reading prayers every time they start activities, instilling the importance of honesty, upholding diversity and respect for others, controlling worship activities with a daily worship book, setting a disciplined learning schedule, getting used to reading the Quran, paying attention to children's socialization in the home and school environment, creating an Islamic environment at home and school. This finding can be used as an example for parents and teachers in raising students with a religious character.